Selection into Short-Time Work and Labor Market Outcomes after the Great Recession - Empirical Evidence using German Micro-Level Data - Sebastian Becker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Short-time work (STW) was one of the most popular labor market policies during the great recession and is considered a main factor of the German Labor Market Miracle. However, little is known about the labor market outcomes of participants after the crisis. Using a unique dataset on STW linked with IAB's Integrated Employment Biographies, I can observe which workers firms selected into the scheme and also observe their labor market outcomes during and after the crisis. Comparing participants and non-participants within firms I find that workers with higher tenure, age, full time jobs and education are more likely to be chosen for STW. Furthermore, participants have by far a higher probability to keep their job.
Keywords: E24; J08; J63; 330